Structural brain correlates of cognitive and behavioral impairment in MND. Issue 4 (2nd February 2016) - Agosta, Federica; Ferraro, Pilar M.; Riva, Nilo; Spinelli, Edoardo G.; Chiò, Adriano; Canu, Elisa; Valsasina, Paola; Lunetta, Christian; Iannaccone, Sandro; Copetti, Massimiliano; Prudente, Evelina; Comi, Giancarlo; et al.
Abstract: Objective: To assess the structural correlates of cognitive and behavioral impairment in motor neuron diseases (MND) using multimodal MRI. Methods: One hundred one patients with sporadic MND (56 classic amyotrophic lateral sclerosis, 31 upper motor neuron phenotype, and 14 lower motor neuron phenotype) and 51 controls were enrolled. Patients were classified into MND with a pure motor syndrome (MND‐motor) and with cognitive/behavioral symptoms (MND‐plus). Cortical thickness measures and diffusion tensor (DT) metrics of white matter (WM) tracts were assessed. A random forest approach was used to explore the independent role of cortical and WM abnormalities in explaining major cognitive and behavioral symptoms. Results: There were 48 MND‐motor and 53 MND‐plus patients. Relative to controls, both patient groups showed a distributed cortical thinning of the bilateral precentral gyrus, insular and cingulate cortices, and frontotemporal regions. In all regions, there was a trend toward a more severe involvement in MND‐plus cases, particularly in the temporal lobes. Both patient groups showed damage to the motor callosal fibers, which was more severe in MND‐plus. MND‐plus patients also showed a more severe involvement of the extra‐motor WM tracts. The best predictors of executive and non‐executive deficits and behavioral symptoms in MND were diffusivity abnormalities of the corpus callosum and frontotemporal tracts, including the uncinate, cingulum, and superior longitudinal fasciculi. Conclusions: Cortical thinning and WM degeneration are highly associated with neuropsychological and behavioral symptoms in patients with MND. DT MRI metrics seem to be the most sensitive markers of extra‐motor deficits within the MND spectrum. Hum Brain Mapp 37:1614‐1626, 2016 . © 2016 Wiley Periodicals, Inc.